2017
DOI: 10.1016/j.foodchem.2017.01.117
|View full text |Cite
|
Sign up to set email alerts
|

A new real-time PCR method for rapid and specific detection of ling ( Molva molva )

Abstract: Seafood fraud - often involving substitution of one species by another - has attracted much attention as it is prevalent worldwide. Whilst DNA analysis has helped to combat this type of fraud some of the methods currently in use are time-consuming and require sophisticated equipment or highly-trained personnel. This work describes the development of a new, real-time PCR TaqMan assay for the detection of ling (Molva molva) in seafood products. For this purpose, specific primers and a minor groove binding (MGB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The results found that the apparent fluorescence signal can be observed in all eight Gadiformes species by adding genomic DNA at levels as low as 0.048 ng (Figure S1). This level was comparable to the LODs of previous studies on other authentication assays using SYBR Green real‐time method (Quek et al , ), but represented a less sensitivity compared with probe‐based real‐time PCR (Prado et al , ; Taboada et al , ). Nevertheless, several advantages, such as the simple design, easy set‐up and low cost, still make SYBR Green method a wide application on food fraud detection (Safdar & Junejo, ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The results found that the apparent fluorescence signal can be observed in all eight Gadiformes species by adding genomic DNA at levels as low as 0.048 ng (Figure S1). This level was comparable to the LODs of previous studies on other authentication assays using SYBR Green real‐time method (Quek et al , ), but represented a less sensitivity compared with probe‐based real‐time PCR (Prado et al , ; Taboada et al , ). Nevertheless, several advantages, such as the simple design, easy set‐up and low cost, still make SYBR Green method a wide application on food fraud detection (Safdar & Junejo, ).…”
Section: Resultssupporting
confidence: 80%
“…As it has been widely discussed (Teletchea et al , ; Rasmussen & Morrissey, ; Böhme et al , ), both nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) are suitable for fish species identification. Although the limitation in the applicability of quantitative approaches has been highlighted (Mohamad et al , ; Amaral et al , ), mtDNA is still preferentially chosen as the target in many studies for qualitative analysis (Prado et al , ; Taboada et al , ; Xiong et al , ), due to the advantages of high mutation rate, multi‐copy nature and maternal inheritance. Moreover, the candidate gene marker should have a high inter‐specific variability and display either low or no intra‐specific variations (Teletchea et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 10 of the samples did not include the scientific name on the label and appeared under the ambiguous name “cod” (Herrero et al., 2010). Taboada, Sánchez, Sotelo et al (2017) tested their assay on 31 commercially relevant ling ( Molva molva ) samples, of which 19.4% were mislabeled. In fact, three of the samples were substituted with other species, with two identified as lower‐value species ( Brosme brosme and Molva dypterigia ) and one identified as a higher‐value species ( Gadus morhua ) (Tabaoda, Sánchez, Sotelo et al., 2017).…”
Section: Fish Orders and Detection Methodsmentioning
confidence: 99%
“…Mmol_Cytb‐R (reverse) 5′‐ATGTTAGTCCTCGTTGTTTAGAGGTATG‐3′) and minor groove binding TaqMan probe (Mmol_Cytb‐P [probe] 5′‐CTAGTTCTCATAGTAGTCCCCT‐3′). Statistically significant differences between Ct value obtained this species (19.45 ± 0.65) and the average Ct of nontarget species DNA (38.3 ± 2.8) (Taboad, 2017)…”
Section: Introductionmentioning
confidence: 96%